Implementasi Peraturan Menteri Negara Pemberdayaan Perempuan dan Perlindungan Anak Nomor 11 Tahun 2011 tentang Pengembangan Kota Layak Anak - Fitri Rizkiani; Rudi Kurniawan; Hadi Iskandar (Asia-Pacific Journal of Public Policy, 2019)
This study reported that the Regulation of the State Minister for Women's Empowerment and Child Protection Number 11 of 2011 concerning Child-Friendly City Development has been executed through the equipment of public facilities for children in the Lhokseumawe city, Aceh Province. However, this program has not effectively been implemented and well-designed. Numerous obstacles are found such as a lack of friendly public spaces supported for children and no restrictions on smoking in public places. Therefore, the improvement and evaluation for the Child-Friendly City Development are needed in the city. This study suggests that the local government should immediately issue a policy on providing free certificates for children and building friendly public spaces. Another effort is to encourage society to actively participated in the program through campaigning the Child-Friendly City Development program. The authors also suggested that if the city is planned to be expanded into a friendly city for children, the local government must fulfill supported public facilities such as schools, libraries, playgrounds, and so on. All facilities must also meet the safety and comfort for children, and be safe from child abuse (e.g., violence, discrimination, racism, sexual abuse, and excessive exposure to children's data).